2007
DOI: 10.1007/s00424-007-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging CFTR in its native environment

Abstract: Application of atomic force microscopy (AFM) on isolated plasma membranes is a valuable method to study membrane proteins down to single-molecule level in their native environment. The cystic fibrosis transmembrane conductance regulator (CFTR), a protein of the adenosine triphosphate-binding cassette transporter superfamily, is known to play a crucial role in maintaining the salt and water balance on the epithelium and to influence processes such as cell volume regulation. A mutation in the gene encoding for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 114 publications
(82 reference statements)
2
24
0
Order By: Relevance
“…Electron microscope studies of purified, antibodydecorated CFTR performed at 2-nm resolution revealed CFTR as a dimer of ellipsoidal form (12 9 10.6 9 16.2 nm) with orifices beneath the putative TMD [28]. Atomic force microscopy (AFM) of immunogold-labeled CFTR on isolated plasma membranes also revealed the CFTR channel as a tail-to-tail dimer with a central pore of unrealistically large (*10 nm) radius [32]. In contrast, single molecule fluorescence imaging in live cells [33] and electron microscopy of two-dimensional CFTR crystals [26] provided evidence for monomeric CFTR.…”
Section: Introductionmentioning
confidence: 95%
“…Electron microscope studies of purified, antibodydecorated CFTR performed at 2-nm resolution revealed CFTR as a dimer of ellipsoidal form (12 9 10.6 9 16.2 nm) with orifices beneath the putative TMD [28]. Atomic force microscopy (AFM) of immunogold-labeled CFTR on isolated plasma membranes also revealed the CFTR channel as a tail-to-tail dimer with a central pore of unrealistically large (*10 nm) radius [32]. In contrast, single molecule fluorescence imaging in live cells [33] and electron microscopy of two-dimensional CFTR crystals [26] provided evidence for monomeric CFTR.…”
Section: Introductionmentioning
confidence: 95%
“…In the present work, we measured the mechanical properties of living BQ2 cells, a stably cystic fibrosis transmembrane conductance regulator [20,56] (CFTR)-overexpressing Chinese hamster ovary (CHO) cell line, as a function of the type and size of the colloidal probe. To analyze the acquired data, we calculated the Young's modulus of the cells by an implementation of the Hertz model.…”
Section: Introductionmentioning
confidence: 99%
“…The low [BPG] in the patient with the G551D mutation possibly results from changed enzyme activities because no differences in erythrocyte physiology were detectable. CFTR is incorporated into the red cell membrane (e. g. [53]), but a relation to BPG metabolism remains speculative.…”
Section: Discussionmentioning
confidence: 99%